1988
DOI: 10.1111/j.1432-1033.1988.tb13966.x
|View full text |Cite
|
Sign up to set email alerts
|

The N‐and O‐linked carbohydrate chains of human, bovine and porcine plasminogen

Abstract: The structures of the N‐and O‐glycans of human, bovine and porcine plasminogen were determined by 500‐MHz 1H‐NMR spectroscopy. The N‐glycans of all three species proved to be of the N‐acetyllactosamine type differing from one another with respect to the sialylation and fucosylation patterns. In the N‐glycan of human plasminogen the two antennae are sialylated with N‐acetylneuraminic acid (NeuAc), whereas in the bovine counterpart both branches carry significant amounts of N‐glycolylneuraminic acid (NeuGc). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…2b ). Among the four mixed N- glycans, i.e ., Hex 5 HexNAc 4 NeuAc 1 NeuGc 1 , Hex 5 HexNAc 4 NeuAc 1 NeuGc 1 + OAc, Hex 5 HexNAc 4 dHex 1 NeuAc 1 NeuGc 1 , and Hex 5 HexNAc 4 dHex 1 NeuAc 1 NeuGc 1 + OAc, only Hex 5 HexNAc 4 NeuAc 1 NeuGc 1 was found on bovine plasminogen and porcine vitronectin 40 41 and mice serum 42 . This is the first time that this type of sialylated N- glycan has been identified in rats.…”
Section: Resultsmentioning
confidence: 95%
“…2b ). Among the four mixed N- glycans, i.e ., Hex 5 HexNAc 4 NeuAc 1 NeuGc 1 , Hex 5 HexNAc 4 NeuAc 1 NeuGc 1 + OAc, Hex 5 HexNAc 4 dHex 1 NeuAc 1 NeuGc 1 , and Hex 5 HexNAc 4 dHex 1 NeuAc 1 NeuGc 1 + OAc, only Hex 5 HexNAc 4 NeuAc 1 NeuGc 1 was found on bovine plasminogen and porcine vitronectin 40 41 and mice serum 42 . This is the first time that this type of sialylated N- glycan has been identified in rats.…”
Section: Resultsmentioning
confidence: 95%
“…However, there are instances where NeuSGc is heterogeneously distributed among the glycan chains of certain glycoconjugates. The sialic acids of 0-linked glycan chains on bovine plasminogen, for example, contain about 94% NeuSAc, whereas the sialic acids on the N-linked chains of the same molecule consist of only 29% Neu5Ac [35]. Similarly, in certain fractions of porcine submandibular mucin, NeuSAc occurs preferentially in a(2 + 3) linkages to Gal while NeuSGc shows a tendency to be bound by x ( 2 -+ 6 ) linkages to GalNAc [36].…”
Section: Specificity ~F Siulyltruns$erase Activity F O R Cmp-neu5 Ac mentioning
confidence: 99%
“…In 1988, a groundbreaking NMR study on the glycosylation of porcine, bovine and human plasmin, revealed the positions and composition of the O - and N -glycans [165]. The now well defined form 1 of human plasmin, in which the N -glycan at Asn288 with terminal sialic acids was altered to a high mannose glycan (GlcNAc 2 Man 9 ), exhibited a k cat / K M of about 6%, due to interference with substrate binding in the kringle 3 domain (Figure 3F) [139,166].…”
Section: Discussionmentioning
confidence: 99%
“…Novel methods or old techniques with new applications may facilitate the analysis of glycans on natural proteins, in particular NMR [165,184]. Thus, we are looking forward to a new era of combined efforts from different structural biological methods, which can elucidate the architecture and behavior of naturally glycosylated proteins.…”
Section: Discussionmentioning
confidence: 99%